The Influence of Selenium on Telomere Length and DNA Damage as Indicators of Age-Related Changes: A Systematic Literature Review - Bohari; Fatimah Fitriani Mujahidah; Erna Susilowati; Marhamah Marhamah; Rimbawan Rimbawan (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The study aimed to analyze the relationship of selenium to telomere length and DNA damage that reflect aging-related changes at the genome and cellular level. This study used the Systematic Literature Review method to summarize evidence regarding the potential of selenium as an anti-aging agent. It was conducted in April and May 2023. The initial stage was to identify research questions consisting of PICO (Population, Intervention, Comparator, and Outcome). The population involved adults and intervened with selenium, did not use a comparator, and used non-epigenetic biomarker outcomes, namely telomere length and DNA damage which reflect aging-related changes at the genome and cellular level. The reviews were obtained from various countries, including Sweden, France, the United States, Australia, and Brazil. The research subjects used were also diverse and at wide intervals, ranging from young people (20-30 years) to adults (> 70 years). A total of 4 of the 7 studies used a cross-sectional study scheme, 1 case-control, and 2 used an experimental design. Adequate selenium intake can potentially affect telomere length and telomere length maintenance. However, the relationship between selenium and telomere length can be affected by other factors, such as the individual's age and health conditions. Selenium intake may be an important factor in maintaining telomere length and preventing age-related diseases.  Selenium supplementation may be beneficial for people with low selenium levels or who are at risk of age-related diseases. Further research is needed to confirm the findings of this study and to determine the optimal dose of selenium for maintaining telomere length.